NatMag cleaner / Hani Hasriena Hasrin ... [et al.] - Hasrin, Hani Hasriena; Ahmad Nizam, Muhammad Firdaus; Ujud, Nur Amalin Batrisya; Khairul Anuar, Deeny Robeatul Adawiyah; Jenal, Norzalina (2021)
Floors are usually affected by dirt, dust, and debris.. The dirtier the floor, the greater the health problems. These provide them a conducive environment to reproduce. Among the cleaning products used to overcome the problems is floor cleaner product which are mostly chemical based. In a typical Palm Oil plantation, almost 70% of the fresh fruit bunches are turned into wastes in the form of empty fruit bunches, fibres and shells, as well as liquid effluent. These by-products can be converted to value-added products or energy NatMag Cleaner, Natural Magnificent Cleaner is a floor cleaning product made of natural ingredients. The main material is the wastes of empty fruit bunches of the palm oil tree. These empty fruit bunches are dried and burnt to ashes and then mixed together blended curry leaves, fragrant lemon grass and pandan leaves. The ashes have the ability to clean heavy dirty stains just by spraying or spreading the powder on the dirty surfaces for a duration of time. The different types of leaves used have the speciality and ability of repelling different type of insects. Mixing them all together enable a multipurpose cleaner to be produced. NatMag Cleaner is an environmentally friendly product. It uses natural resources which can abundantly found in Malaysia. It is the first ever floor cleaning product using the waste of palm oil empty fruit branches as the main materials. This product also supports the government efforts to enhance the usage of Malaysian natural resources and which has been one of the country's agenda. It also supports the recycle campaigns launched by the government. And most important, it is a Malaysian product that can be proud of.